Digital Religion In Pakistan: Role Of SNS In Influencing Religious Practices Of University-Going Females Of Punjab, Pakistan - Kiran Iqbal, Saima Kausar, Mudassar Hussain Shah (Migration Letters, 2024)
Digital media has therefore become one of the most powerful tools of conveying information and shaping opinions of people in matters that affect their lives, and therefore their thinking and doings. This has a huge effect of religious practices because it has opened up new channels through which people can participate in the production, distribution and use of religious material. This study looks into the topic that is becoming more and more important: what transforms in religious practices of female university students in Punjab, Pakistan because of digital media? It is therefore important to understand and gain insight on how these digital platforms moderate religiosity given the fact that they dominate communication and information dissemination today. As a theoretical framework, the Uses and Gratification Theory which postulates that people consciously use media to get specific needs met including spiritual and religious needs forms the base for the research. This study was conducted using sample of the University of Sargodha in order to analyze the impact of digital media in modern society about religious practices, religious groups, and religious text. Measures for Digital Media Consumption and facets of religious life were analyzed for correlation. Findings suggest some significant relationships and it is evident from the evidence outlined above that young Pakistani women’s religious experiences are mediated through digital media. These observations contribute to continuing understanding of the link between religion and digital technology, and stress the importance of understanding how media in digital format contribute to modern religious practices.